Antioxidant potential and health benefits of bitter gourd (Momordica charantia L.) - Kumari, Preeti; Verma, R B; Nayik, Gulzar Ahmad; Solankey, S S (Journal of Postharvest Technology, 2017)
In recent years, there has been a great deal of attention toward the field of free radical chemistry. Free radicals reactive oxygen species and reactive nitrogen species are generated by our body by various endogenous systems, exposure to different physiochemical conditions or pathological states. A balance between free radicals and antioxidants is necessary for proper physiological function. Public awareness of the purported health benefits of dietary antioxidants has increased the demand for fruit and vegetable products with recognized and improved antioxidant quality and has created new opportunities for the horticulture industry to improve fruit and vegetable quality by enhancing antioxidant content. This review describes the vegetables specially bitter gourd’s antioxidants, namely vitamin C, carotenoids, phenolics, Flavonoid, vitamin A, B, and E. Bitter gourd is a powerful nutrient-dense plant composed of a complex array of beneficial compounds. These include bioactive chemicals, vitamins, minerals and antioxidants which all contribute to its remarkable versatility in treating a wide range of illnesses. The fruits contain high amounts of vitamin C, vitamin A, vitamin E, vitamins B 1,B2 and B3, as well as vitamin B9 (folate). Medicinal value of bitter melon has been attributed to its high antioxidant properties due in part to phenols, flvonoids, isoflavones, terpens, anthroquinones, and glucosinolates, all of which confer a bitter taste. Bitter gourd fruit have anti-oxidant, anti-microbial, anti –viral activities and also used as a very popular traditional medicine in India, China and Central America for diabetes, it has also other important health promoting substances such as vicin, charatine and polypeptide-p.In view of potential use of bitter gourd fruit in the traditional medicine, its therapeutic benefits and bioactive compounds warrant furtherinvestigation.